Reduced Inflammation and Tissue Damage in Transgenic Rabbits Overexpressing 15-Lipoxygenase and Endogenous Anti-inflammatory Lipid Mediators - Serhan, Charles N; Jain, Ashish; Marleau, Sylvie; Clish, Clary; Kantarci, Alpdogan; Behbehani, Balsam; Colgan, Sean P; Stahl, Gregory L; Merched, Aksam; Petasis, Nicos A; Chan, Lawrence; Van Dyke, Thomas E (The Journal of immunology (1950), 2003)
PGs and leukotrienes (LTs) mediate cardinal signs of inflammation; hence, their enzymes are targets of current anti-inflammatory therapies. Products of arachidonate 15-lipoxygenases (LO) types I and II display both beneficial roles, such as lipoxins (LXs) that stereoselectively signal counterregulation, as well as potential deleterious actions (i.e., nonspecific phospholipid degradation). In this study, we examined transgenic (TG) rabbits overexpressing 15-LO type I and their response to inflammatory challenge. Skin challenges with either LTB4 or IL-8 showed that 15-LO TG rabbits give markedly reduced neutrophil (PMN) recruitment and plasma leakage at dermal sites with LTB4. PMN from TG rabbits also exhibited a dramatic reduction in LTB4-stimulated granular mobilization that was not evident with peptide chemoattractants. Leukocytes from 15-LO TG rabbits gave enhanced LX production, underscoring differences in lipid mediator profiles compared with non-TG rabbits. Microbe-associated inflammation and leukocyte-mediated bone destruction were assessed by initiating acute periodontitis. 15-LO TG rabbits exhibited markedly reduced bone loss and local inflammation. Because enhanced LX production was associated with an increased anti-inflammatory status of 15-LO TG rabbits, a stable analog of 5S,6R,15S-trihydroxyeicosa-7E,9E,11Z,13E-tetraenoic acid (LXA4) was applied to the gingival crevice subject to periodontitis. Topical application with the 15-epi-16-phenoxy-para-fluoro-LXA4 stable analog (ATLa) dramatically reduced leukocyte infiltration, ensuing bone loss as well as inflammation. These results indicate that overexpression of 15-LO type I and LXA4 is associated with dampened PMN-mediated tissue degradation and bone loss, suggesting that enhanced anti-inflammation status is an active process. Moreover, they suggest that LXs can be targets for novel approaches to diseases, e.g., periodontitis and arthritis, where inflammation and bone destruction are features.